Politik Uang dan New Normal dalam Pemilu Paska-Orde Baru - Muhtadi, Burhanuddin (Integritas : Jurnal Antikorupsi, 2019)
How many voters sell their votes in Indonesia, and how effective is it? Elaborated from a wide range of survey methods Ã¢â‚¬â€whether individual, observational, or derived from the list-experiment, the proportion of voters participating in vote-buying in the 2019 election was between 19,4% and 33,1%. This range is comparatively high by international standards, with IndonesiaÃ¢â‚¬â„¢s level of vote buying being the third largest in the world. Given that the list-experiment and the straight-forward survey questions result inconsistent findings, it can be concluded that vote buying is less likely to be stigmatized, and such practice has become a new normal during the election. This study also finds that IndonesiaÃ¢â‚¬â„¢s open-list proportional system shapes the supply-side of vote buying. Under such an electoral system, candidates are forced to compete against co-partisans for personal votes. And because, according to the open-list system, a seat (or seats) secured by a party must be allocated to that partyÃ¢â‚¬â„¢s candidates who obtained the most individual votes, candidates only need to win a small slice of the votes to defeat their co-partisans. To do so, they need to differentiate themselves from their party peers, including by buying votes. Keywords: Vote Buying, Intra-Party Competition, Open-List Proportional System